2022
DOI: 10.1186/s13058-022-01550-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility landscape and active transcription factors in primary human invasive lobular and ductal breast carcinomas

Abstract: Background Invasive lobular breast carcinoma (ILC), the second most prevalent histological subtype of breast cancer, exhibits unique molecular features compared with the more common invasive ductal carcinoma (IDC). While genomic and transcriptomic features of ILC and IDC have been characterized, genome-wide chromatin accessibility pattern differences between ILC and IDC remain largely unexplored. Methods Here, we characterized tumor-intrinsic chrom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…9a–c ). A previous study in which TCGA–BRCA ATAC-seq data were reanalysed revealed that the FOXA1 motif was more enriched in ER + /HER2 − invasive ductal carcinoma (IDC) tumours than in ER + /HER2 − invasive lobular carcinoma (ILC) tumours [ 26 ]. The JFCR–BRCA cohort included two ILC tumours, which were all assigned to CA-B; therefore, we conducted differential analysis between CA-A and CA-B but only for IDC tumours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9a–c ). A previous study in which TCGA–BRCA ATAC-seq data were reanalysed revealed that the FOXA1 motif was more enriched in ER + /HER2 − invasive ductal carcinoma (IDC) tumours than in ER + /HER2 − invasive lobular carcinoma (ILC) tumours [ 26 ]. The JFCR–BRCA cohort included two ILC tumours, which were all assigned to CA-B; therefore, we conducted differential analysis between CA-A and CA-B but only for IDC tumours.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, ATAC-seq was used to profile 410 tumour samples from 23 cancer types at The Cancer Genome Atlas (TCGA), including 75 BC samples [ 25 ]. Although these data have already been utilised in another study [ 26 ], patient stratification of BC via ATAC-seq has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the MLP model, critical genes such as TNNT1 [37, 38] and AQP7 [39–41] were also identified as potential therapeutic targets. Five genes ( TACC3 [4245], CDC20 [46–50], FOXI1 [5153], KIF11 [5457], and MKI67 [17, 1921]) were identified as critical in both the LOG and MLP models and have been proposed to be therapeutic targets, with MKI67 being particularly noteworthy because it encodes the Ki-67 protein. Additionally, our analysis employing the CNN model identified several key genes as potential therapeutic targets for breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Five genes (TACC3 [42][43][44][45], CDC20 [46][47][48][49][50], FOXI1 [51][52][53], KIF11 [54][55][56][57], and MKI67 [17,[19][20][21])…”
Section: Biological Relevancementioning
confidence: 99%
“…The hazard agents that must be highlighting it are epidemiological agents "such as age, obesity, alcohol use, and exposure to estrogen in lifetime", but history of family for breast carcinogenesis have more strongest one. Nearly "20%" for carcinomas "family origin", as well as following the presence of "specific predisposing gene" for disease occurring (19,20,21).…”
Section: Family History and Genetic Factors In Breast Cancermentioning
confidence: 99%